INFLUENCE OF LATERAL DISPLACEMENT OF BOGIES ON THE FREIGHT CAR DYNAMICS - Shvets, A. O (Science and Transport Progress, 2021)
Purpose. The work is aimed at determining the influence of the lateral displacement of a freight car bogie, taking into account the value of the movement speed on its main dynamic indicators and interaction indicators of the rolling stock and the track. Methodology. The quantitative assessment of dynamic indicators was obtained by the method of mathematical and computer modeling. The design scheme of the car takes into account the interaction peculiarities of cars as part of the train: the possibility of all modes of body vibration in space, the transmission of longitudinal force from neighboring cars in vertical and horizontal directions, taking into account the technical condition of individual parts of the car and their design features, as well as various operating conditions. Findings. During the research, a mathematical model of a coupling of five freight cars was applied to study the dynamic loading of a gondola car and a track. Main dynamic and interaction indicators of the rolling stock and the track in case of transverse bogie displacement when moving along curved track sections assessment were assessed. The maximum possible values of the lateral displacement of the freight car bogie were substantiated. Originality. The mathematical model of the coupling of freight cars in the train has been improved. In the calculation schemes describing the vibrations of the cars, the peculiarities of the freight car bogies, lozenging of the bogie side frames are taken into account. The model makes it possible to study the effect of changing rotation angle of the central axis of the car body, which in turn leads to the lateral displacement of bogies relative to each other, on the main dynamic and interaction indicators of the rolling stock and the track. For the first time, the influence of transverse displacement of the bogie was investigated, taking into account the wear of its parts and assemblies when moving on track sections with unevenness. Practical value. The calculation results can be used to assess the influence of the bogie transverse displacement on the dynamic qualities of the rolling stock and interaction indicators of the rolling stock and the track, taking into account the wear of parts and units of the bogie when moving in straight and curved track sections with irregularities. The application of the results obtained will contribute to an increase in the stability of freight rolling stock in the conditions of increasing travel speeds, which in turn will allow developing technical conditions for the implementation of resource-saving technologies for transporting goods that meet the safety requirements of train traffic.